Implementation of the Rahn Agreement at Bank Jatim Syariah Sampang - Rosi, Fahrur; Matnin, Matnin; Semi, Semi; Rosi, Rosi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
This research aims to determine the implementation of the rahn contract at the Bank Jatim Syariah Sampang Bank. This research approach is an object of field research using a qualitative approach, namely a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The results of research regarding the Implementation of the Rahn Agreement at Bank Jatim Syariah Sampang as follows: first, the pawn financing procedure: has fulfilled the administrative requirements and complies with the harmony and conditions of the rahn, such as; Prospective customers submit requests for pawn financing facilities, valid identification (KTP), and collateral to the pawn party. The pawn party assesses the collateral that has been submitted by the prospective customer and the loan nominal is based on the estimate. Second, delivery of pawned goods as collateral for debt; Loans by pawning goods as collateral for debts in the form of rahn are permitted by law, and practices that follow sharia principles as stated in Article 1 of the DSN-MUI Fatwa Number: 26/DSN-MUI/III/2002. Third; Determination of maintenance rental fees; Maintenance and storage fees are ujrah that customers must pay every ten days, based on the amount depending on the value of the customer's loan. Yet the maintenance and storage costs for marhun do not follow the provisions of paragraph 4 of the DSN-MUI fatwa Number 25/DSNMUI/III/2002.